Theoretical research of the processes to reduce the concentration of chlorinated compounds with natural fibers - Andriulaitytė, Ieva; Valentukevičienė, Marina; Zigmontienė, Aušra (International Conference “Environmental Engineering”, 2023)
Disinfectants based on chlorine are the most commonly applied biocides for public spaces disinfection. Various studies show the use of sodium hypochlorite went up several times during the pandemic. Chlorinated compounds after they enter stormwater react with organic, inorganic and anthropogenic pollutants there and form harmful disinfection by-products. The article aims to present theoretical research of the processes linked to reduce the chlorinated compounds concentrations in stormwater. Research theory is based on the scientific information and the experiments’ results. The equations of mass transfers are used to describe the process. Analysis is focused on the case when chlorinated compounds concentrations in stormwater change depending on mass transfer from solution to filter fiber. Experiments present that after filtration with natural fibers the amount of disinfectants in stormwater decreased approximately 60 percent. The values of mass transfer reveal the efficiency of hemp and peat fibers to transport chlorinated compounds (C22H48ClN). Research found out the values of different filter materials are quite similar: 0.20 Def.·106, cm2s–1 (hemp) and 0.19 Def.·106, cm2s–1 (peat).